2020
DOI: 10.1016/j.jhin.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial COVID-19: experience from a large acute NHS Trust in South-West London

Abstract: Summary Transmission of Coronavirus Disease 2019 (COVID-19) in healthcare settings has significant implications for patients and healthcare workers, can amplify local outbreaks, and place additional burden on already stretched resources. Risk of missed or late diagnosis of COVID-19 was high during the United Kingdom’s initial ‘containment phase’, because of strict criteria for testing. The risk remains due to asymptomatic/pre-symptomatic transmission, complicated by challenges faced with laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 3 publications
1
49
0
1
Order By: Relevance
“…8 Applying a similar case definition, Taylor et al found probable nosocomial cases represented 11.3% of confirmed cases within a major London trust admitted between 6 th March to 12 April 2020; mortality was unreported in this study. 7 These reports preceded recognition of high-profile nosocomial outbreaks across several UK hospitals. 15,16 Thus, reliable estimates of the true impact of hospital-acquired covid-19 infection remain hampered by a paucity of publicly-available data at national and regional levels.…”
Section: Introductionmentioning
confidence: 99%
“…8 Applying a similar case definition, Taylor et al found probable nosocomial cases represented 11.3% of confirmed cases within a major London trust admitted between 6 th March to 12 April 2020; mortality was unreported in this study. 7 These reports preceded recognition of high-profile nosocomial outbreaks across several UK hospitals. 15,16 Thus, reliable estimates of the true impact of hospital-acquired covid-19 infection remain hampered by a paucity of publicly-available data at national and regional levels.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, healthcare workers (HCWs) may be routinely tested to prevent nosocomial transmission to patients who may have other comorbidities 2,3 . Both of these populations have a substantially higher risk of fatality from COVID-19 infection than the general population 4,5 . In the UK, testing commonly uses polymerase chain reaction (PCR) to detect the presence of viral RNA in the nasopharynx of those sampled 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Most COVID-19 transmission studies to date have utilised epidemiological analysis alone to identify outbreaks, including those from the UK (6) (7), China (8), France (9) and South Korea (10). The main limitation with using epidemiology alone is that when point prevalence is high, for instance at 2.2% in London during the first wave in April 2020 (11), this increases the chance two people in epidemiological contact are independent cases.…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial infection is reported to account for around 10-20% of all confirmed cases (18) (19) (6) (20) often in designated outbreaks (6) (7) (8) (9) (10) and with a crude death rate of up to 30% (19). The most likely routes of transmission are between patients and involving healthcare workers (HCW), with potential for all combinations of directionality to occur within the same nosocomial cluster.…”
Section: Introductionmentioning
confidence: 99%